Salivary leptin and TAS1R2/TAS1R3 polymorphisms are related to sweet taste sensitivity and carbohydrate intake from a buffet meal in healthy young adults - Han, Pengfei; Keast, Russell S. J.; Roura, Eugeni (British journal of nutrition, 2017)
The influence of sweet taste sensitivity on food intake is not well understood. We investigated the involvement of salivary leptin and SNP of the sweet taste receptor genes (TAS1R2/TAS1R3) on sweet taste sensitivity, sensory-specific satiety (SSS) and macronutrient intake in healthy human adults. In all, nineteen high sweet sensitivity (HS) and eleven low sweet sensitivity (LS) subjects were classified based on the sweetness perception of one solution (9 mm sucrose) forced-choice triangle test. All participants completed a randomised crossover design experiment where they consumed one of three iso-energetic soup preloads differing in primary taste quality (sweet, non-sweet taste-control or no-taste energy-control). A period of 1 h after the preload, participants were offered a buffet meal consisting of foods varying in taste (sweet or non-sweet) and fat content. Subjective measures included hunger/fullness and SSS for sweetness. Saliva and buccal cells were collected to measure leptin level and to study the TAS1R2/TAS1R3 specific SNP, respectively. Salivary leptin concentrations were significantly higher in LS than HS participants (P<0·05). In addition, HS showed stronger sweet SSS compared with LH participants (P<0·05), and consumed less carbohydrate (% energy) and more non-sweet foods than LS (P<0·01 and P<0·05, respectively). Alleles from each TAS1R2 locus (GG compared with AA alleles of rs12033832, and CT/CC compared with TT alleles of rs35874116) were related to higher consumption of carbohydrates (% energy) and higher amount of sweet foods, respectively (P<0·05). In contrast, no associations were found for the TAS1R3 alleles. These results contribute to understand the links between taste sensitivity, macronutrient appetite and food consumption.